The Influence of Integrated Instructional Design of Environmental Education and Teaching Modules in IPAS Learning on Environmental Literacy (Ex Post Facto Method Analysis in the Context of the Merdeka Curriculum) - Ony Widyastuti; Agung Purwanto; Ananto Kusuma Seta (Eduvest - Journal of Universal Studies, 2024)
This research explores the impact of implementing Instructional Design and Teaching Module devices in Natural and Social Sciences (IPAS) education, in line with the Merdeka Curriculum, on environmental literacy in primary schools. The aim of this research is to determine the influence of Integrated Environmental Education IPAS Instructional Design and IPAS Teaching Module in IPAS learning on students' environmental literacy at the primary school level. The research method employs an ex post facto approach to identify and analyze the influence of these variables after implementation, without direct intervention in the learning situation. The results show that both instructional devices significantly contribute to students' environmental literacy. Students' environmental literacy learning outcomes in IPAS education using the Integrated Environmental Education IPAS Instructional Design (average score of 80) are better compared to IPAS Teaching Module (69). In conclusion, the research findings indicate that Integrated Environmental Education IPAS Instructional Design significantly positively influences the improvement of students' environmental literacy compared to IPAS Teaching Module.